Reevaluating the So-Called "Reforms of Urukagina" (1) Social Justice, Vertical Solidarity and Reciprocity - Schrakamp, Ingo (Zeitschrift für altorientalische und biblische Rechtsgeschichte, 2024)
This paper analyses the so-called “Reform Texts” of Urukagina. It identifies be6 -lu5 -da u4 -be2 -ta and nam tar-ra u4 -be2 -ta as key terms which contrast the “former regulations”, upheld by Urukagina’s predecessors, with the “pristine order” established by the gods. It is argued that these orders had been out of joint upon Urukagina’s accession, that Urukagina claims their harmonization via his role as king, and that vertical solidarity or reciprocity represents a governing principle among the social, ethical, and juridical implications of the pristine order. Therefore, instead of interpreting Urukagina’s acts as a restoration or reformation, an interpretation as “readjustment” is proposed.